Woven Carbon Fiber Epoxy Composite Laminates Reinforced With Carbon Nanotube Interlayer Using Electrospray Deposition Method - Zakaria, Muhammad Razlan (2020)
The hybridization of woven carbon fiber-carbon nanotube (CF-CNT) received enormous attention from research communities in the field of epoxy laminates composites. In this study, electrospray deposition (ESD) method was used to deposit carbon nanotube (CNT) on the woven carbon fiber (CF) surface. The deposition of the CNT on the woven CF surface is intended to improve the surface roughness of the woven CF as well as to provide a mechanical interlocking between the woven CF and the epoxy matrix. For ESD method, the stability of the CNT in the solvent is very crucial during the ESD process and N-Methyl-2-Pyrrolidone is proven suitable for dispersing CNT due to high stability. The effect of voltage and spray time of ESD on the morphologies of the woven hybrid CF-CNT has been studied. The optimum voltage and spray time to achieve homogeneous and even CNT coating on the woven CF surface is 15 kV and 15 min, respectively. From single fiber test, the ESD method is found to be safe without any significant degradation on the tensile strength of the woven CF-CNT. The epoxy composite laminates with optimized woven hybrid CF-CNT and woven CF without deposited CNT were then prepared and compared in terms of mechanical, thermal and dielectric properties. The evaluation showed that woven hybrid CF-CNT epoxy composite laminates have greater mechanical, thermal and dielectric properties than woven CF epoxy composite laminates. The results demonstrate that the woven hybrid CF-CNT epoxy composite laminates are capable of improving tensile strength, tensile modulus, flexural strength, flexural modulus,interlaminar shear strength, thermal conductivity and dielectric constant about 21 %, 37 %, 19 %, 27 %, 25%, 35 % and 22 %, respectively, compared to the woven CF epoxy composite laminates.